2023
DOI: 10.1186/s12957-023-03076-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis of patients with stage IIIC1p cervical cancer treated by surgery

Abstract: Background Cervical cancer (CC) is one of the most common gynaecologic malignancies. The prognosis of stage IIIC1p cervical cancer patients treated by surgery is heterogeneous. Therefore, the aim of this study was to analyse the factors influencing the prognosis in such patients. Methods From January 2012 to December 2017, 102 patients with cervical cancer who underwent surgical treatment in the Department of Gynaecology and Tumours, Changzhou Mate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Fan et al. found that no postoperative adjuvant therapy was an independent risk factor for poor OS and DFS in patients with stage IIIC1p cervical cancer ( 9 ). Simultaneous dual-platinum-based chemotherapy and pelvic radiation therapy could be a potential approach to enhance results in these patients ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fan et al. found that no postoperative adjuvant therapy was an independent risk factor for poor OS and DFS in patients with stage IIIC1p cervical cancer ( 9 ). Simultaneous dual-platinum-based chemotherapy and pelvic radiation therapy could be a potential approach to enhance results in these patients ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al. found that NLR>3.8 were independent risk factors for OS and DFS in patients with stage IIIC1p cervical cancer ( 9 ). Increased MLR indicated an increased in monocytes and a decrease in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations